Curcumin-cinnamaldehyde hybrids as antiproliferative agents against women’s cancer cells - Anselmo, Daiane B. [UNESP]; Polaquini, Carlos R. [UNESP]; Marques, Beatriz C. [UNESP]; Ayusso, Gabriela M. [UNESP]; Assis, Letícia R. [UNESP]; Torrezan, Guilherme S. [UNESP]; Rahal, Paula [UNESP]; Fachin, Ana L.; Calmon, Marília F. [UNESP]; Marins, Mozart A.; Regasini, Luis O. [UNESP] (Springer Nature, 2021)
Curcumin and cinnamaldehyde are natural products whose antineoplastic activity has been well explored in biological evaluations. However, their poor chemical stability under physiological conditions has been an obstacle to their use as therapeutic agents. Herein, we designed and synthesized two series of curcumin-cinnamaldehyde hybrids by removing reactive functionalities, including β-diketone and aldoxyl moieties. All compounds were evaluated by the MTT assay to determine their antiproliferative activity against women’s cancer cells. Compound 5a (3′-hydroxychalcone) demonstrated potent antiproliferative activity against all cancer cell lines tested, with IC50 values ranging from 2.7 to 36.5 µM. Compound 5a was more active and selective than curcumin and cinnamaldehyde (parent compounds) against the CaSki, SiHa, C33, and A431 cell lines, displaying a higher selectivity index (SI = 8.5) than curcumin (SI = 0.8) toward the non-tumorigenic HaCaT cell line. Clonogenic experiments indicated that compound 5a inhibited A431 colony formation in a concentration-dependent manner. In addition, 5a was more stable than its parent compounds in pH 7.4 at 37 °C. In silico investigations suggested that 5a has good drug-likeness properties. In conclusion, our results indicate the use of curcumin and cinnamaldehyde as parent compounds for the design of hybrids with attractive antiproliferative activity and chemical stability.
Keywords: Antiproliferative; Cancer; Cinnamaldehyde; Curcumin; Hybridization